Impact of adoption of improved varieties of chikpea (Cicer arietinum) on yield and income in Madhya Pradesh - RIMAL, NARAYAN SHARMA; KUMAR, SHIV; CHAHAL, V P; SINGH, VIKRAM (The Indian Journal of Agricultural Sciences, 2015)
The adoption pattern of improved varieties of chickpea (Cicer arietinum L.) and their impact on farm income in Madhya Pradesh with 100 chickpea growing households spread over Vindhyan, Malwa and Bhagelkhand regions for the survey period of 2012-13 provided insight into the incidence and intensity/ penetration power of varieties in seed supply chain and increase in overall chickpea production in the state. Farmers of Vindhyan and Bhagelkhand regions mostly preferred desi varieties as they adopted JG 315 followed by JG 335, Ujjan 21 and JG 11, while Dollar and KAK 2 were dominant kabuli varieties in Malwa region. In general, the average price of kabuli chickpea was 31.17% higher than desi chickpea. In case of kabuli chickpea, the net revenue from Dollar variety was about 10% more than that obtained from KAK2.The physical and financial performance of JG 315 and Ujjain 21 were also better compared to other varieties in Vindhyan and Bhagelkhand regions. As a result of adoption of improved varieties the seed replacement rate of pulses has increased from 2.15% in 2002 to 11% in 2012. The major constraints expressed by farmers in adoption of improved varieties of chickpea included: low awareness of the new varieties; lack of pest resistant varieties; non availability of seeds of improved varieties; lack of access to credit; high cost of seed; and lack of short or extra short duration varieties. The paper recommends putting in place a system for demonstrating the production potential of the new and promising chickpea varieties and providing timely information, credit, inputs and market support to accelerate the adoption and production of chickpea in the state. The results also provide deep insight to stakeholders of chickpea not only to penetrate in seed markets but also help in deciding how to design R&D program as well.